Differences in Expression and Function in the Atrium versus Ventricle of the Sodium-Calcium Exchanger in the Embryonic Chicken Heart. (1st September 2013) - Polo-Parada, Luis; Modgi, Amol A.
Abstract : Heart function is well known to be dependent on intrinsic electrical activity. This electrical activity is primarily mediated by a combination of interactions among various ionic channels and transporters. In this study, we demonstrate that the Na + -Ca 2+ exchanger (NCX) is equally present in both atrial and ventricular cells at early stages of development (st. 13). However, ventricular cells exhibit an increase in NCX messenger ribonucleic acid (mRNA) levels during later stages of development, while levels in atrial cells remain constant. We demonstrate that the current density of the NCX increases with development in the ventricle but remains constant in the atrial cells. Furthermore we demonstrate that the NCX has a major role in shaping the cardiac action potential at early stages mainly in ventricular cells (st. 14) than later mainly in the atrial cells (st. 30).